The Influence of Employee Welfare and Organizational Culture on Work Loyalty: JEL Classification: J28, M12, M14, M54 - Veranita Veranita; Nurmadhani Fitri Suyuthi; Mujahid Mujahid (Journal La Bisecoman, 2025)
This study aims to analyze and examine the influence of transformational leadership and The purpose of this study is to analyze the effect of employee welfare on work loyalty at the Airport Authority Office of Region V Makassar, to analyze the effect of organizational culture on work loyalty at the Airport Authority Office of Region V Makassar, and to analyze the simultaneous effect of employee welfare and organizational culture on employee work loyalty at the Airport Authority Office of Region V Makassar. In this study, the population consisted of all employees working at the Airport Authority Office of Region V Makassar, totaling 164 individuals. The population focused on Civil Servants (PNS), amounting to 164 employees. This research employed a quantitative approach with a survey method. Primary data were collected through questionnaires. The sample size was determined using the Slovin formula, resulting in 116 respondents. The research instrument was tested for validity and reliability, as well as for classical assumptions including normality, multicollinearity, and heteroscedasticity. Data analysis was conducted using multiple regression analysis. The findings reveal that employee welfare has a positive and significant effect on work loyalty at the Airport Authority Office of Region V Makassar. Organizational culture also has a positive and significant effect on employee work loyalty. Simultaneously, employee welfare and organizational culture have a positive and significant effect on work loyalty among employees at the Airport Authority Office of Region V Makassar. The coefficient of determination (R Square) value of 0.375 indicates that 37.5% of the variation in work loyalty can be explained by these two variables, while the remaining variation is influenced by other factors outside the research model.